Partisipasi Masyarakat dalam Melakukan Konservasi Peninggalan Sejarah di Kawasan Wisata Candi Ceto dalam Perspektif Pendidikan Karakter - Emy Wuryani; Nani Mediatati (Cakrawala: Jurnal Pendidikan, 2019)
This research aims: 1) Explain the factors that encourage people to participate in conservation of historical heritage. 2) Identify the character values that form the basis of community participation in conservation. 3) Identify forms of historical heritage conservation activities. 4) How to carry out conservation. The techniques of data collection are literature, observation, FGD, and depth interviewing. The basis of analysis used of qualitative descriptive. The results of this research as follows: 1) The factors that encourage community participation in conservation: (a) cultural factors as ancestral heritage, historical heritage must be secured, cared for and preserved; (b) Social psychology: safeguarding and caring for historical heritage, their life will be safe and the environment will bring prosperity to peoples. 2) Character values that form the basis community participation in conservation are responsibility, sincerity, humanity, and care for the environment. 3) The forms of conservation activities show as to take care of and finding historical heritage, checking historical heritage, preserving, caring for the environment and historical sites so that clean, keeping the path to the location of historical sites so that clean and accessible to visitors.